Physicochemical Characterization and Corrosion Inhibition Potential of Ficus benjamina (FB) Gum for Aluminum in 0.1 M HCl - EDDY, Nnabuk Okon; AMEH, Paul Ocheje; IBRAHIM, Ali (Walailak Journal of Science and Technology (WJST), 2014)
Examination of the physical (colour, odour, pH, solubility in various solvent) and chemical (GCMS and FTIR) characteristics of Ficus benjamina gum revealed that the gum is yellowish in colour, mildly acidic and ionic in nature. Major constituents of the gums were found to be sucrose and d-glucose, which constituted 60.92 % of its chemical constituents while various carboxylic acids (albietic acid (1.00 %); hexadecanoic acid (4.41 %); 9-octadecanoic acid (1.00 %), stearic acid (3.01 %); oleic acid (0.10 %); octadecanoic acid (9.12 %) and 6,13-pentacenequinone (20.43 %) accounted for the remaining constituents. Functional groups identified in the gum were found to be those typical for other carbohydrates. From the knowledge of the chemical structures of compounds that constitutes the gum, the corrosion inhibition potentials of the gum was ascertained and from weight loss analysis, the gum was found to be an active inhibitor against the corrosion of aluminum in solutions of tetraoxosulphate (VI) acid. The gum acted as an adsorption inhibitor that favours the mechanism of chemical adsorption and supported the Frumkin and Dubinin-Radushkevich adsorption models. doi:10.14456/WJST.2015.94